Parallel robot for 3D additive manufacturing - Zhang, Xiang Bin (2015)
3D printing through the years has gain lots of attention and interest. With the increasing focus in this sector, the future research and improvement will be based on the methods of printing and the 3D printer itself. Current 3D printers are constructed based on an x-y-z gantry architecture and are thus slow due to the stack-up configuration. On the other hand, parallel robot offers high speed and acceleration characteristics. It also offers a movement of the platform in the shortest route possible. This enhances the speed of the 3D printing process which in turn helps to increase productivity and efficiency. This report will focus on the development of an unconventional 3D printer based on parallel robot architecture which provides movement in a 6 dimensional spaces. This robot will be modified from the original delta robot and with the combination of knowledge from delta robot and steward platform, the new 6 degree of freedom robot is introduced. With the introduction of the RSS (Revolute, Spherical, and Spherical) configuration, the 6 link robot prototype is able to perform the 6 degree of freedom movement. This includes the conventional x-y-z movement and the advance rolling, pitching and yawing movement. With the combination of the NI CVI programming, automation of the robot is made possible. The basic automation shown in this report’s programming chapter will include the homing process, the (x, y, z) movement and also the angle orientation of the platform which allows it to perform rolling, pitching and yawing. Forward and inverse kinematic analyses are done in this report to provide the understanding of the position analysis of the joint, link and platform. Prototyping is also described in this report to provide the physical study, understanding and demonstration of the 6 link free form robot. Circuit connection, designing of the prototype components and programming are all included in the different chapters of this report for detail understanding of this robot. Further improvement and work are also included in the conclusion section of this report.